Pengaruh Modal Kerja Terhadap Profitabilitas Pada Koperasi Bangkit di Rangkasbitung - Lita Mulyati; Dede Suharna; Arini Piandika; Maesaroh .; Hayatinufus Siatan (E-Journal Studia Manajemen, 2014)
The level of efficiency of a business can be seen by comparing the profits obtained by the total amount of capital spent to acquire the profit of each period. Net profit indicates the profitability of the company. Profit reflects the return to equity holders for the period. Sources of financing for working capital in the cooperative using its own working capital and foreign working capital. This study uses a quantitative method of statistical analysis using the sample as much as 10 years from 2004 to 2013 and using data collection techniques documentation spss version 20. Based on the results obtained by the working capital impact the profitability of 0.034% and the rest is influenced the other, meaning that the hypothesis is accepted.